Using Explosive Strength Exercises for Improving Wheelchair Basketball Scoring in Iraqi National Basketball Players - Alani, Yasser; Hameed, Huda (Journal of Physical Education, 2022)
The research aimed at designing explosive strength exercises that is important in scoring in wheelchair basketball as well as identifying the use of these exercises on improving wheelchair basketball. The researchers used the experimental method on (12) wheelchair basketball players who participated in Asian championship. The data was collected and treated using SPSS to conclude that explosive strength have a significant effect on scoring performance. Finally, the researcher recommended that coaches and teachers should use explosive strength exercise to develop scoring performance in wheelchair basketball players.